So different yet so alike: Micro and macro labour market outcomes in Germany and Spain - Maia Güell; Cristina Lafuente; Manuel Sánchez; Hélène Turon (SERIEs - Journal of the Spanish Economic Association, 2022)
It is well known that German and Spanish labour markets are quite different from a macro point of view. In this paper, we look at these markets through the lenses of individual unstable spells. These include all forms of atypical employment (such as temporary contracts and mini-jobs) as well as unemployment. This combined unstable state captures a fuller picture of the individual experience of volatile income and uncertain employment status than unemployment alone. We find that the survival rates of unstable spells in the two countries are much more similar than those from unemployment. This suggests that the usual focus on unemployment stocks and durations exaggerates the contrast between the two countries in terms of workers' experience of instability. We place these findings in the context of very similar aggregate shocks in the two countries and different policy choices on labour market reforms.
Keywords: J21; J64; J80; 330; Administrative social security data; Atypical employment; duration; Mini-jobs; Temporary contracts; Unstable spells